A Study of Vertical Load Capacity of Carbon Fiber Concrete Piles Reinforced with Geosynthetics - El-Kasaby, El-Sayed A.; Roshdy, Mohab; Emara, Noaman A. (International Journal of Advanced Engineering, Management and Science, 2023)
A compressive static load test was conducted on a total of thirteen end-bearing carbon fiber concrete piles reinforced with geosynthetics, which were divided into four groups and compared to traditional reinforced concrete piles. The tested piles included one reference concrete pipe pile reinforced with traditional steel reinforcement, four concrete pipe piles partially reinforced with carbon fiber bristles with different percentages of 0.75%, 1.00%, 1.25%, and 1.50% of cement weight, four piles partially reinforced with the same carbon fiber bristles percentages and confined with triaxial geogrid, and four piles partially reinforced with the exact carbon fiber bristle percentages and reinforced with carbon fiber bars. Thirteen vertical static loading tests (SLTs) were conducted on 1050-mm-long pipe piles with a diameter of 150 mm to obtain the behavior of these composite piles. Furthermore, the traditional method of stress-strain curves was analyzed. Comparisons between curves were conducted. It was concluded that the use of these composite piles significantly increased the ultimate vertical load capacity by up to 39%. Pile ductility was also significantly improved, and this composite material could be perfectly applied in geotechnical conditions. In addition, an economic analysis was conducted.